Autobiographical Imprints in Nineteenth-Century Canadian Drama: Sarah Curzon's Laura Secord: Heroine of 1812 - Boyko-Head, Christine (Theatre Research in Canada / Recherches théâtrales au Canada, 2001)
This essay examines Sarah Anne Curzon’s artistic and political “obsession” with the story of Laura Secord. The essay argues the potential for auto/biographical criticism and performance theory to (re)create a point of access into Curzon’s work that suggests a personal bond between the mythic heroine and the 19th-century woman writer. Cette communication analyse "l’obsession" politico-artistique de Sarah Anne Curzon à travers l’histoire de Laura Secord. Elle met en évidence le potentiel de la critique auto/biographique et de la théorie de la performance afin d’introduire un point de départ qui interroge le lien personnel et étroit entre l’héroïne mythique et l’auteur de la pièce du 19ème siècle.